Merrymaking and Militia Musters: Mohawks, Loyalists, and the (Re)Construction of Community and Identity in Upper Canada - Paxton, James (Ontario History)

(untitled) (The Ontario Historical Society, 2010)
The American Revolution not only divided families, friends, and neighbours; it also gave rise to new communities. For Mohawks and loyalists who campaigned together out of Fort Niagara, the war forged them into a multi-ethnic military community. Survivors who resigned themselves to exile in scattered settlements across Upper Canada maintained their distinct community through regular rounds of private and semipublic celebrations – parties, reunions, militia musters – and commonplace acts of hospitality. These forms of entertainment preserved familiar social arrangements in an alien environment, but they also provoked a challenge from the colonial government which sought to impose a conservative order on the province.